Entrepreneurial Development in a National Basis (2010)
This paper presents the use of innovative educational methodology, by the CDEE-ICESI, to spread entrepreneurial education and assistance to young entrepreneurs living in different cities of Colombia. Web CT and Internet were used as educational technology tools with designs and application specifically developed for the Colombian users by CDEE staff